Gadget Usage and Its Relationship with Mental and Emotional Health in Early Childhood (3–6 Years) at Puskesmas Medan Tuntungan (Sumatera Medical Journal, 2026)
Introduction: Excessive gadget use in early childhood is increasingly associated with cognitive, behavioral, and emotional problems. Preschool-aged children are particularly vulnerable as this period involves rapid socio-emotional and motor development. Objective: This study aimed to determine the association between gadget use and mental and emotional health among children aged 3–6 years at Puskesmas Medan Tuntungan. Methods: A cross-sectional study was conducted involving 105 children selected through consecutive sampling. Data on gadget use (duration, type, ownership, and age of first exposure) were collected using parent-reported questionnaires. Mental and emotional status was assessed using the KMME instrument. Bivariate analysis was performed using the Chi-square test with a significance level of p < 0.05. Results: Most children (61.90%) used gadgets for more than one hour per day, exceeding recommended limits. A total of 64 children (60.95%) screened positive for mental and emotional problems. Screen time >1 hour was significantly associated with mental–emotional problems (p = 0.001). No significant relationship was found between personal gadget ownership and mental–emotional problems (p = 0.729). Conclusion: Longer screen time, particularly >1 hour per day, was significantly associated with mental and emotional problems in preschool-aged children. Further longitudinal studies with larger samples are needed to strengthen causality and generalizability.